(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive guide to understanding and practicing the three main types of vowel sounds in English: monophthongs, diphthongs, and triphthongs. It breaks down each category, explaining how each sound functions and offering practical exercises to help learners improve their pronunciation. The piece emphasizes the importance of clear vowel sounds for effective communication and offers specific techniques, like using minimal pairs and shadowing practice, to help learners master each type of sound. Through this structured approach, readers can develop greater accuracy and confidence in their spoken English. The article concludes by encouraging learners to persist in their practice, reinforcing that mastering these sounds is a key step toward fluent, natural-sounding English.